Doing Business in Russia from the Perspective of a Czech Company - Remizov, Gleb (2017)
This bachelor thesis focuses on doing business in Russia from the perspective of a Czech company. The main objective is to depict the business environment of Russia and its beer market for a Czech beer company. The first part concentrates on general information about Russia and a specific sector of its economy. Second part focuses on the conditions of entry to the Russian beer market, risks and opportunities for a Czech company. In the third part there is a summary of a research and relevant conclusions to it.